The colorectal surgeon’s personality may influence the rectal anastomotic decision - Moug, Susan; Henderson, N.; Tiernan, J.; Bisset, C.N.; Ferguson, Eamonn; Harji, D.; Maxwell-Armstrong, C.; MacDermid, E.; Acheson, A.G.; Steele, R.J.C.; Fearnhead, N.S. (Wiley, 2018)
Aim. Colorectal surgeons regularly make the decision to anastomose, defunction or form an end colostomy when performing rectal surgery. This study aimed to define personality traits of colorectal surgeons and explore any influence of such traits on the decision to perform a rectal anastomosis.